Urban Development - Hamdani, Chayma (New Jersey, USA Lanrye International, 2015)
Urban planning plays a significant role in the development of nations. Cities are rising as never before and these days, it is assumed that at least 50% of the world's population lives in urban cities. This movement is projected to carry on, and at the same time, the problems in urban areas are also expected to increase. Urbanization constitutes a compound procedure linking problems with communal, financial, ecological and spatial proportions that need suitable solutions. This book highlights some of these problems and discusses potential solutions in terms of organization, planning and management.
Keywords: Urban economics; Economics; Business & Economics